Tartary Buckwheat: An Under-utilized Edible and Medicinal Herb for Food and Nutritional Security. Issue 4 (19th May 2022) - Ruan, Jingjun; Zhou, Yuexia; Yan, Jun; Zhou, Meiliang; Woo, Sun-Hee; Weng, Wenfeng; Cheng, Jianping; Zhang, Kaixuan
ABSTRACT: The nutritional value of Tartary buckwheat is much higher than that of common buckwheat. Tartary buckwheat is rich in nutrients, some of them unique, and has good medicinal properties. It also serves as a good feed crop. This review aims to provide an up-to-date and comprehensive literature on Tartary buckwheat's active substances (proteins, polyphenols, D-chiro-inositol, fat-soluble substances, resistant starch, dietary fiber, minerals and vitamins), medicinal value (e.g., prevention of AIDS, and prevention and treatment of cancer, and cardiovascular and cerebrovascular diseases) and nutritional effects (as an antioxidant, in lowering blood pressure, blood fat, and blood sugar, for detoxification and weight loss), etc., and research activities connected to Tartary buckwheat and its health effects in China and abroad. This review is expected to present a reference for the further development and utilization of Tartary buckwheat.